Romania Regional Hospital Analysis Study : Regional Referral Networks in Romania - World Bank Group (World Bank, Washington, DC, 2018)
Romania lags behind other European Union (EU) countries in many health outcomes. The government of Romania plans to build three new regional hospitals in the North-West (NW), North-East (NE), and South-West (SW) regions. These are envisaged to be tertiary referral hospitals providing highly complex care to their region. Five or six further regional hospitals may follow this first batch. Regional hospitals are not just bricks and mortar, but the apex of a complex regional health system. As flagship public hospitals, regional hospitals are planned to be the hub of each regional health system. Work to date, however, has focused on design and construction rather than how regional hospitals will interact and coordinate with other facilities. To highlight factors in the wider health system that are crucial to the role of regional hospitals, the World Bank undertook a comprehensive assessment of regional referral networks in Romania. This report drew on available hospital activity data, stakeholder interviews, and literature review to assess the extent to which these factors are in place using tracer conditions, such as total knee replacements and stroke. In conclusion, without as much attention to coordination of care within regional health networks as construction of regional hospitals, the hospitals will not be able to fulfil their promise as flagship providers of complex care.